The health locus of control in middle-aged low-risk patients qualified for coronary artery bypass grafting with extracorporeal circulation - Pielok, Joanna; Płotek, Włodzimierz; Samborska, Regina; Cybulski, Marcin (Journal of Medical Science, 2016)
Introduction. The health locus of control gives a possibility to determine the patient’s self-efficacy resources, which are specific in locating health control actions. It also enables prediction of the type of health behaviours the patient will exhibit during recovery after a cardiac surgery.Aim. The aim of the study was to use the Multidimensional Health Locus of Control (MHLC) to assess the occurrence of the internal health locus of control (IHLC), powerful others (PHLC) and chance (CHLC) in patients undergoing coronary artery bypass grafting according to their sex, occupational activity and education. The occurrence of types of health locus of control was also assessed.Material and methods. 52 patients aged 47–63 years were tested (46 men – 88.5% and 6 women – 11.5%). The position of health control was tested by means of the Polish version of the American MHLC adapted by Juczyński.Results. The average scores were as follows: I – 27.92 points, O – 29.60 points, C – 22.61 points. The research revealed statistical dependencies for some MHLC dimensions and for the sex and education. MHLC Type 7 – undifferentiated, strong (19 patients, 36.6%) was the most common.
Keywords: anaesthesia; locus of control